Analisis Keadilan Pajak Terhadap UMKM Fashion di Marketplace dalam Perspektif Undang-Undang HPP - Siti Asyiah; Putri Fitria Nurwati; Mariani Mariani; Ali Murtadho (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The growth of fashion UMKM in Indonesia through digital marketplace platforms has made a major contribution to the national economy, especially in job creation and developing creative product exports. However, this development also presents new challenges in the field of taxation, especially after the enactment of Law No. 7 of 2021 concerning the Harmonization of Tax Regulations (UU HPP). This study aims to analyze the principle of tax fairness for fashion UMKM operating through marketplaces, reviewed from a normative legal approach. The appointment of the market as a VAT collector and the continued implementation of Final Income Tax raises the potential for a double burden and inconsistency with the principles of vertical and horizontal justice in taxation. The results of the study show that the regulations in the Law on HPP do not fully reflect justice, legal certainty, and legal benefits, and risk pushing UMKM towards informality. Therefore, it is necessary to adjust technical policies that are more proportional to the capacity of UMKM actors, in order to realize an inclusive and equitable taxation system.